Long Range Contacts in Overlay Networks with Unbalanced Node Distribution - Araújo, Filipe (2004)
A fundamental aspect in the design of overlay networks is the path length/node degree trade-off. Previous research has shown that it is possible to achieve logarithmic path lengths for logarithmic or even constant node degree. While nearby contacts, with nodes that have close identifiers, ensure a connected lattice of nodes, short path lengths demand for the use of long range contacts. In this respect, previous work exhibits limitations in scenarios where node distribution is unbalanced: either short path length properties do not hold or may require node degree and/or signaling to grow with respect to the virtual identification space instead of the number of nodes (which is usually several order of magnitudes smaller). This paper proposes and evaluates a new mechanism to establish long range contacts in unbalanced overlay networks. This mechanism does not need any kind of manual configuration to adapt to different network configurations and is oblivious to the virtual identification space. Experimental comparison with previous work suggests that our mechanism achieves logarithmic path lengths with respect to the number of nodes, but regardless of node distribution in the virtual identification space